Antecendents and Consequences of Trust in Diamond Industry - Shah, Naitik (2008)
Trust is one of the most important factors in any sort of business. Especially in an industry like Diamond Industry, the whole business runs on the basis of trust. Hence, it becomes very important to understand the antecedents of the trust and the consequences of increased trust to make better management decision. This dissertation makes an effort to explore the various antecedents and consequences of trust in a B2B and a B2C market (diamond industry). The dissertation starts with an overview of the diamond industry in India and a brief introduction to the topic. Literature review is then used to study the research that has already been conducted on the topic in the past. Literature review is followed by a creation of a research framework based on the literature. Mixes of qualitative and quantitative research methods have been used for this dissertation. The results from the research are then analysed followed by conclusion, managerial implications and the scope for future research.